The Correspondence between Roberto Gerhard and Arnold Schoenberg - Ortiz-de-Urbina, Paloma (Journal of the Society for Musicology in Ireland, 2014)
On 18 October 1923 Roberto Gerhard wrote a long letter to Arnold Schoenberg asking to be accepted as his pupil. Two weeks later he received a positive answer and left for Vienna at once. There he met Schoenberg and began a master-pupil relationship that would gradually turn into deep friendship, as attested by fifty-three extant letters written between 1923 and Schoenberg’s death in 1951. Existing in archives in several countries and, for the most part, as yet unpublished, these letters provide a wealth of information about Gerhard’s personal life and professional career, with interesting insights into Gerhard’s compositional process.